Use of infrared thermography to estimate enteric methane production in dairy heifers. Issue 3 (27th May 2022) - Gabbi, Alexandre M.; Kolling, Giovani J.; Fischer, Vivian; Pereira, Luiz Gustavo R.; Tomich, Thierry R.; Machado, Fernanda S.; Campos, Mariana M.; Silva, Marcos V. G. Barbosa da; Cunha, Camila S.; Santos, Manoela K. R.; McManus Pimentel, Concepta M.
ABSTRACT: The trial aimed to investigate the use of infrared thermography (IRT) to estimate enteric methane production in dairy heifers. The study lasted 5 days with 36 Gyr, Gyr x Holstein and Holstein heifers. The sulphur hexafluoride (SF6 ) tracer technique was used to estimate methane emission. Superficial body temperature was obtained with an infrared camera (FLIR® T300) on each side of the animals at 20-minute intervals during eight hours after the morning feeding. Data were analysed using Pearson's correlation analysis and multivariate regression analysis, as well as two multivariate tests to investigate the relationship with methane emission. The analysis considered all the data together (total) and three subsets: initial (0–150 minutes), middle (150–300) and final period (300–442 minutes after feeding). Based on R 2 and canonical correlations, the best predictive capacity of methane emission by IRT occurred in the initial and final periods after feeding. Infrared thermography may be a good estimator of methane emission using the SF6 -tracer technique when considering the flanks' temperature.